A Methodology for the Development of Web-based Information Systems: Web Development Team Perspective - Abdul-Aziz, Azlianor; Koronios, Andy; Gao, Jing; Sulong, Muhammad Suhaizan (2012)
Web engineering has evolved through software engineering due to the technological changes from traditional information systems to web-based services. It has powered the Internet and World Wide Web technologies in which it has reflected the use of web-based information systems to reach broader audiences, new markets, access more information and interact in real time across barriers. The need for a methodology to develop such web-based information systems is inevitable, to enable adaptation of the traditional approach of systems analysis and design that is the software development life cycle (SDLC) to shift into a new paradigm namely the web-based development life cycle (WDLC). In this paper, the literature review has discovered a general methodology for WDLC that differs in terms of the number of stages and the nature of the development environment compared to the SDLC approach. However, from the insights of web development team through case studies, it is found that there is a collective agreement that having comprehensive development stages can satisfy their clients. The reason is their clients seem to believe that, if a smaller number of development stages exist to build web-based information systems, this can really reduce the development costs and time leading to faster delivery to the market.